(untitled) (World Economics and Finance Bulletin, 2026)
This paper will examine how digital marketing can be used to add value to a brand with emphasis on the moderating contribution of smart business environment using the case of Key Card Iraq. The key question of the study is as follows: How successful is digital marketing in influencing the brand value with the help of the smart business environment? The research adopted a descriptive-analytical methodology since it relied on a questionnaire to gather information on a sample of 90 administrative leaders (managers and their assistants) in the company. The SPSS statistical software was used in data analysis. The findings proved that the digital marketing, in its different forms, has a substantial positive effect on increasing the brand value in the smart business environment as a mediating factor. This highlights the critical value of incorporating digital practices and smart environments in increasing the perceived brand value. This research proposes the need to incorporate a model that integrates digital marketing policies and smart business environment application within a holistic management model to ensure that the overall effect of the two on enhancing brand value is maximized